Mechanical Response of Mudstone Based on Acoustic Emission Fractal Features - Xianyin Chang; Yunpei Liang; Qican Ran (Fractal and Fractional)
In this study, the effect of the stress amplitude on the mechanical behavior of mudstone was systematically investigated by cyclic loading and unloading experiments and acoustic emission (AE) monitoring. The results show that at low-stress amplitudes, mudstone specimens show better elastic recovery ability, lower damage accumulation and higher structural stability. At high-stress amplitudes, the irreversible damage of the mudstone increases significantly, the internal fractures gradually expand and penetrate through, and the risk of instability increases significantly. This is manifested by the gradual increase in cumulative irreversible strain of mudstone at different stress amplitudes, up to 0.144%. In addition, different stress amplitudes have significant effects on energy evolution characteristics, with low-stress amplitudes mainly showing elastic deformation and a high percentage of recoverable energy, while high-stress amplitudes show a high percentage of dissipated energy. Under the condition of high-stress amplitude, such as the mudstone specimen #4, the percentage of tensile failure is 81.15%. Tensile failure dominates at all stress amplitudes, where the failure mechanism within mudstone is mainly characterized by the extension of tensile-type fractures. Through the multifractal analysis of AE signals, this study reveals the effect of the stress amplitude on the fracture extension mode and failure mechanism of mudstone. As the stress amplitude increases, Δα and Δf show an increasing trend. This indicates that the fracture extension process transforms from a relatively homogeneous and simple mode to a more inhomogeneous and complex mode. This transformation reflects the nonlinear and multiscale fracture characteristics of mudstone under high-stress conditions. The results of this study help to understand the mechanical behavior of mudstone under cyclic loading during coal mining and provide theoretical support for safe coal production.